Discovery of candidate genes involved in ethylene biosynthesis and signal transduction pathways related to peach bud cold resistance - Xia, Wenqian; Yang, Yupeng; Zhang, Chenguang; Liu, Chunsheng; Xiao, Kun; Xiao, Xiao; Wu, Junkai; Shen, Yanhong; Zhang, Libin; Su, Kai (Frontiers in Genetics, 2024)
Low temperature pose significant challenges to peach cultivation, causing severe damage to peach buds and restricting production and distribution. Ethylene, an important phytohormone, plays a critical role in enhancing plant cold resistance. Structural genes and transcription factors involved in ethylene biosynthesis and signal transduction pathways are associated with cold resistance. However, no research has specifically addressed their roles in peach cold resistance. Therefore, in this study, we aimed for cold-resistance gene discovery in cold-sensitive peach cultivar '21Shiji' (21SJ) and cold-resistance cultivar 'Shijizhixing' (SJZX) using RNA-seq and gas chromatography. The findings revealed that under cold stress conditions, ethylene biosynthesis in 'SJZX' was significantly induced. Subsequently, a structural gene, PpACO1-1, involved in ethylene biosynthesis in peach buds was significantly upregulated and showed a higher correlation with ethylene release rate. To identify potential transcription factors associated with PpACO1-1 expression and ethylene signal transduction, weighted gene co-expression network analysis was conducted using RNA-seq data. Four transcription factors: PpERF2, PpNAC078, PpWRKY65 and PpbHLH112, were identified. These findings provide valuable theoretical insights for investigating the regulatory mechanisms of peach cold resistance and guiding breeding strategies.